Payment Card Network Pricing - A Theoretical Approach Analyzing the Relationship between Downstream Market Characteristics and the Merchant Usage Fee - Markus Langlet (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
In this thesis the model of a payment card network is constructed to explore the impact of downstream market characteristics (i.e., the market where merchants and consumers interact) on the merchant and the interchange fee, thereby extending the literature's observations of payment systems. To accomplish this, three scenarios are analyzed: firstly, a unitary payment card network with merchants under Cournot quantity competition and, secondly, under Bertrand price competition respectively, as well as, thirdly, a multi-party payment card network with merchants under Cournot quantity competition. This study yields two significant results. Firstly, the merchant and the interchange fee are found decreasing in the consumer price elasticity, the level of product substitutability and the relative frequency of card usage. Secondly, regulating the interchange fee and the merchant fee respectively is found particularly useful since, in markets with less competition where consumers already face inefficiently high prices, the payment card fees will also tend to be higher.
Additional information: zugl. Dissertation, EBS Universität für Wirtschaft und Recht, Wiesbaden, 2011
Keywords: D53; G21; L11; L4; 650; Two-sided markets; Payment card networks; Platform pricing; Bertrand competition; Industrial Organization; Cournot competition; Zwei-seitige Märkte; Zahlkartennetzwerke; Bertrand Wettbewerb; Corunot Wettbewerb